2002
DOI: 10.1109/lsp.2002.800507
|View full text |Cite
|
Sign up to set email alerts
|

A novel full-search vector quantization algorithm based on the law of cosines

Abstract: Vector quantization (VQ) is an essential tool in signal processing. Although many algorithms for vector quantizer design have been developed, the classical generalized Lloyd algorithm (GLA) is still widely used, mainly for its simplicity and relatively good performance. Using law of cosines this letter presents a simple improved method for nearest-neighbor search in GLA. Experiments show that the proposed algorithm outperforms the traditional GLA.Index Terms-Fast nearest-neighbor search, law of cosines, vector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…In the previous work [2], a FS-equivalent search method is proposed. By using the law-of-cosines, d(u i , v) can also be expressed as…”
Section: Previous Workmentioning
confidence: 99%
See 2 more Smart Citations
“…In the previous work [2], a FS-equivalent search method is proposed. By using the law-of-cosines, d(u i , v) can also be expressed as…”
Section: Previous Workmentioning
confidence: 99%
“…Let h 1 be the angle between (u i , x) and h 2 be the angle between (v, x), the previous work [2] has shown that h P |h 1 À h 2 | so that cos(h) 6 cos(h 1 À h 2 ) holds because the cosine is an even function and monotonically decreases over [0°, 90°] interval. Based on the discussions above, Mielikainen proposed a very computationally inexpensive estimation for d( Fig.…”
Section: Previous Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The TIE based fast search algorithms [6]- [13] require 2N additional memory. The search algorithms in [15] and [19] require and additional memory, respectively, where is the total number of vectors in a training sequence.…”
Section: A Algorithmmentioning
confidence: 99%
“…In the search process, codevectors are rejected from being searched through based on an inequality defined by the stored norms and the norm of the training vector. In [15], the distances from training vectors to origin, their squares, sines and cosines are calculated and stored in a pre-defined data structure. An inequality of cosines law was used to reduce the codevector searching area of the full search process.…”
Section: Introductionmentioning
confidence: 99%